PENGUJIAN ARUS MENGGUNAKAN SENSOR SCT 013-000 PADA PEMBANGKIT LISTRIK TENAGA SURYA BERBASIS INTERNET OF THINGS - Alfi Maghfirah; Akhmad Zainuri; Onny Setyawati (Jurnal Mahasiswa TEUB, 2023)
The Internet of Things (IoT) has grown rapidly over the past few years following the increasing demand in communication and control for various devices and gadgets. A key requirement implemented for modern IoT devices is to provide effective connectivity to ensure long-distance communication and data transfer in a wireless environment. Solar power is an energy source that will never run out. This energy can also be used as an alternative energy that is converted into electrical energy, using solar panels. The performance of a solar panel can be determined by measuring its output parameters such as voltage, current, and power. The voltagecurrent characteristics of solar panels are influenced by several factors, including the intensity of solar radiation and the operating temperature of the solar panels. This system is designed to monitor the current using the SCT 013-000 sensor using a microcontroller that communicates serially with ESP32 and implements a monitoring database to display the current on the android application, namely Solar Home System. The results of receiving data from the microcontroller to transfer data to the database by connecting the internet network. The results of the study found that current measurements using the SCT 013-000 sensor obtained a current accuracy value of 99,5%. Keywords: solar panel, monitoring, sensor, accuracy